Superior vena cava stenosis at site of intersection of two pacing electrodes. Issue 4 (October 1979) - Pauletti, M; Pingitore, R; Contini, C
Abstract : Superior vena cava obstruction is described in a patient with two endocardial pacing electrodes. At necropsy a severe stenosis of the venous lumen was found at the site of intersection of the two catheters. There was no evidence of thrombus formation. Venous wall stenosis is an unusual complication of transvenous pacing and is probably favoured by the presence of two electrodes.